Association between admission serum potassium concentration and the island sign on cranial CT in HICH patients: a cross-sectional study - Wang, Yanglingxi; Chen, Peng; Liang, Yidan; Deng, Yongbing; Zhou, Weiduo (Frontiers in Neurology, 2024)
Objective This study aimed to explore the correlation between serum potassium (K+) concentration upon admission and the presence of the Island Sign (IS) in cranial CT scans of patients diagnosed with Hypertensive Intracerebral Hemorrhage (HICH), including the potential presence of a non-linear relationship. Methods This investigation constituted a single-center cross-sectional study. We systematically gathered comprehensive general clinical characteristics, biological indicators, and imaging data from a cohort of 330 patients diagnosed with HICH. These patients received treatment within the neurosurgery department of Chongqing Emergency Medical Center during the period spanning from July 1, 2018, to July 7, 2023. Our primary objective was to scrutinize the potential connection between serum K+ concentration upon admission and the presence of the IS observed in cranial CT scans. To meticulously address this inquiry, we employed logistic regression modeling, thereby meticulously evaluating the correlation aforementioned. Moreover, in order to delve deeper into the intricacies of the relationship, we extended our analysis by employing a smoothed curve-fitting model to meticulously authenticate the potential non-linear interrelation between these two critical variables. Results In this investigation, a total of 330 patients diagnosed with HICH were ultimately enrolled, exhibiting an average age of 58.4 ± 13.1 years, comprising 238 (72.1%) males and 92 (27.9%) females. Among these participants, 118 individuals (35.7%) presented with the IS upon admission cranial CT scans, while 212 patients (64.3%) did not exhibit this characteristic. Upon comprehensive multifactorial adjustments, a non-linear association was uncovered between serum K+ concentration and the presence of IS. Notably, an inflection point was identified at approximately 3.54 mmol/L for serum K+ concentration. Prior to the patient’s serum K+ concentration reaching around 3.54 mmol/L upon admission, a discernible trend was observed—every 0.1 mmol/L increment in serum K+ concentration was associated with an 8% decrease in the incidence of IS (OR: 0.914, 95% CI: 0.849–0.983, p = 0.015). Conclusion The findings of this study underscore a negative association between reduced serum K+ concentration upon admission and the occurrence of the IS on cranial CT scans among patients diagnosed with hypertensive cerebral hemorrhage. Furthermore, this negative correlation appears to manifest within the realm of a non-linear relationship. This study elucidates the potential significance of serum K+ concentration levels among patients with HICH, highlighting the role they play. Moreover, the maintenance of a physiological equilibrium in serum K+ concentrations emerges as a conceivable protective factor for individuals within the stroke population.